If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -4 + 6r = -4 Reorder the terms: -4 + r + 6r = -4 Combine like terms: r + 6r = 7r -4 + 7r = -4 Add '4' to each side of the equation. -4 + 4 + 7r = -4 + 4 Combine like terms: -4 + 4 = 0 0 + 7r = -4 + 4 7r = -4 + 4 Combine like terms: -4 + 4 = 0 7r = 0 Solving 7r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Divide each side by '7'. r = 0 Simplifying r = 0
| 64s^2-4t^2= | | -3(2x-1)=x+10 | | -16x=-8+24x^2 | | 3x+9=-111-9x | | -2x=36 | | 5x=2y+4 | | -5-3x=5x+10 | | x^2-12x+c=0 | | 8x^2-24x-32=0 | | X-0.2x=18 | | -2x^2+18=0 | | w^2+18w+81= | | 12x+71=5 | | 5x+193=13x-7 | | 3x+x=52 | | 12xy=384 | | 6a-a^2=48 | | 215-2x=34x+23 | | 130-3x=42x+15 | | (3x+2)(2x-5)=0 | | 3x+12=-27-1-10x | | x+x=36 | | 36a^2-25b^2= | | 3x+12=27-10x | | 68-3x=6x+19 | | 60-x=5 | | -.5(x+4)=16 | | x+4=24 | | -1/8=2(x-1) | | 9-8x=105-29x | | 2(x^2-4x-4)+x=x(x+47x)-45x | | -27-9=7x+21 |